The impact of university education upon digital start-ups - Ratzinger, Daniel (2017)
With a worldwide shift towards a knowledge economy, universities are seen as a fundamental driver of economic growth. While previous studies have focused on universities’ more direct commercialisation activities, this research investigates the relatively unexplored influence of university education upon graduate entrepreneurship. By considering the digital economy, this exploratory study examines a fast growing sector where knowledge is considered to be a core asset.